2023
DOI: 10.1002/bse.3489
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain entrepreneurship roles for circular supply chain transition

Abstract: The transition to a circular supply chain (CSC) is a prerequisite to establish sustainability in the supply chain. Blockchain‐based CSC enables stakeholders to effectively manage their decision‐making processes, increase revenue, reduce time and costs and ensure information synchronisation. Blockchain start‐ups play an essential role in facilitating the transition from a linear to a circular economy while supporting the development of CSCs. This research aims to explore the role of blockchain entrepreneurship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 149 publications
0
4
0
Order By: Relevance
“…As a result, sustainable solutions may be culminated into enhanced levels of green innovation. This inference is supported by prior research, for instance, Kayikci et al [40] contended that through utilizing blockchain, big data analytics, and AI, entrepreneurs can invoke sustainable solutions through advancements in technology, which can result in improved operational efficiency in the course of sustainable ventures.…”
Section: Serial Mediating Impacts Of Green Entrepreneurship and Green...mentioning
confidence: 73%
See 1 more Smart Citation
“…As a result, sustainable solutions may be culminated into enhanced levels of green innovation. This inference is supported by prior research, for instance, Kayikci et al [40] contended that through utilizing blockchain, big data analytics, and AI, entrepreneurs can invoke sustainable solutions through advancements in technology, which can result in improved operational efficiency in the course of sustainable ventures.…”
Section: Serial Mediating Impacts Of Green Entrepreneurship and Green...mentioning
confidence: 73%
“…Furthermore, Saura et al [39] substantiated that the application of digital technologies in green ventures facilitates circular economy practices by leveraging the optimization of resource re-use and the enhancement in energy efficiency. This is also endorsed by Kayikci et al [40], whereby blockchain technology offers enhanced transparency and traceability, which result in improved operational efficiency and sustainable practices. In addition, the research by Bickley et al [41] identified AI and big data analytics as positive predictors of sustainable entrepreneurship.…”
Section: Impact Of Digital Economic Transformation On Green Entrepren...mentioning
confidence: 90%
“…Traditional banking and financial systems often involve numerous intermediaries, each adding time and cost to transactions [ 60 ]. Blockchain technology can streamline these processes and reduce or even eliminate the need for intermediaries, leading to significant cost savings [ 36 , [61] , [62] , [63] ]. Furthermore, this aspect of blockchain ensures the integrity of data in environments where mutual trust might be lacking, thereby allowing for transactions to be conducted with greater confidence.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing global competition has led businesses to take a more methodical approach to Supply Chain Integration (SCI), which has led them to re-evaluate cooperative supply partnerships based on mutual benefit and joint process improvement [1,2].…”
Section: Introductionmentioning
confidence: 99%